Global trends in research on cervicogenic headache: a bibliometric analysis - Xu, Yu; Gao, Ying; Jiang, Lin; Wu, Lunhui; Yin, Jing; Yang, Zhijun; Dong, Youkang (Frontiers in Neurology, 2023)
Background There has been a marked increase in cervicogenic headaches in recent years, significantly affecting sufferers’ daily lives and work. While several treatments exist for this type of headache, their long-term effects could be improved, and additional data from large clinical samples are needed. This study aims to systematically examine the current state of research in cervicogenic headaches through a bibliometric analysis, identify areas of current interest, and provide insight into potential future research directions. Methods This article examines research trends in the field of cervicogenic headache through a bibliometric analysis of scholarly articles in the field of cervicogenic headache over the past four decades. The bibliometric analysis method employed included searching the Web of Science database using topics related to cervicogenic headaches. Inclusion criteria were limited to articles and review papers on cervicogenic headaches published between 1982 and 2022. The retrieved dataset was then analyzed using R software and VOSviewer to identify the major research areas, countries and institutions, the most influential authors, journals and keywords, co-citations in the literature, and co-authorship networks. Results This study analyzed 866 articles published between 1982 and 2022, involving 2,688 authors and generating 1,499 unique author keywords. Neuroscience and neurology were the primary focus, with participation from 47 countries, primarily led by the United States, which has the most published articles (n = 207), connections (n = 29), and citations (n = 5,238). In the cervicogenic headache study, which involved 602 institutions, the University of Queensland received the most significant number of citations (n = 876), and Cephalalgia was the journal with the most published articles and received the most local citations (n = 82) and highest growth (n = 36). Two hundred sixty-nine journals have published articles on cervicogenic headaches. Among researchers studying cervicogenic headache, Sjaastad O had the most published articles (n = 51) and citations (n = 22). The most commonly occurring keyword was “cervicogenic headache.” Except for the fourth most impactful paper, as determined by the Local Citation Score, which analyzed clinical treatments, all the top documents emphasized investigating the diagnostic mechanisms of cervicogenic headache. The most commonly occurring keyword was “cervicogenic headache.” Conclusion This study used bibliometric analysis to provide a comprehensive overview of the current research on cervicogenic headaches. The findings highlight several areas of research interest, including the need for further investigation into the diagnosis and treatment of cervicogenic headaches, the impact of lifestyle factors on cervicogenic headaches, and the development of new interventions to improve patient outcomes. By identifying these gaps in the literature, this study provides a foundation for guiding future research to improve the diagnosis and treatment of cervicogenic headaches.